Different Ways of Thinking Latin American Development - Madoery, Oscar (Revista del CLAD Reforma y Democracia, 2015)
This paper offers a look from development epistemology, with the purpose of identifying different ways to think the regional reality. The challenge relies on recognizing these understanding fields about Latin American history and reality; ways of interpretation updated in new answers to old questions in relation to the Latin American problem and that bring together different theories and stances, from which initiatives are projected and actions orientated. They are not the only ones, consequently this description is not exhaustive; and areas of contact between them exist. But they use to favor one interpretative concept: Latin America as a territory of absence, of concealment or otherness. They express controversial and open process. But they also express a dispute over the sense of development, sometimes updating positions meaning social rise as the neo-developmentalism, others seeking to re-signify the meaning of the anti-capitalist struggle, as the XXIth century socialism, and sometimes from an alternative world view to the occidental civilization, as the Good Living (Buen Vivir).All together, they offer a political interpretation of the development problem, given by the reach of the country projects prevailing along history, the way of solving conflicts, the risks taken by the public agendas, the ways of reproduction, regulation and relations prevailing in each moment, the social and territorial integration, the connection to the world system. The principal Latin American contribution to the development theory is that it rises from concrete practice of the situated subjects, of the social actors, and of the people in their struggles and substantial aspirations. Development as a category of situated politics expresses a point of view focused in the individuals and in the people in their living places, among their relations, their tensions, their attachments and their creations. A thinking appeared from experience contexts, that acknowledges exogenous conditioning, but that emerges from the territory where rises its alternative strength.
Keywords: Development Styles; Development Strategy; Development Problem; Perspectives; Latin America